Determination of Antiviral Mechanism of Centenarian Gut-Derived Limosilactobacillus fermentum Against Norovirus - Li, Ying; Gao, Junshan; Xue, Liang; Shang, Yanyan; Cai, Weicheng; Xie, Xinqiang; Jiang, Tong; Chen, Huizhen; Zhang, Jumei; Wang, Juan; Chen, Moutong; Ding, Yu; et al. (Frontiers in Nutrition, 2022)
Although noroviruses are the causative agents of most non-bacterial foodborne disease outbreaks, effective antivirals are currently unavailable. Certain probiotic strains have been reported as active antivirals for norovirus infections, but their mechanisms have not been fully elucidated. Herein, we examined the antiviral potential of 122 lactic acid bacteria isolates against murine norovirus (MNV), a human norovirus surrogate. A centenarian gut-derived strain, Limosilactobacillus fermentum PV22, exhibited the strongest MNV antagonism and reduced the viral titer by 2.23 ± 0.38(log-value) in 5 min with stable activity at 25 °C (P < 0.01). Genome mining revealed that its antiviral activity can be attributed to the synthesis of γ-aminobutyric acid, and this finding was experimentally verified. Furthermore, we demonstrated the safety of the isolate and its high intestinal colonization ability. In conclusion, we discovered a centenarian gut-derived L. fermentum strain with strong anti-norovirus activity and identified its antiviral metabolite. Our results will offer new solutions for the prevention and treatment of food-related norovirus infections.